Awareness among health professionals to reduce programmatic vulnerabilities in leprosy - Rodrigues Pires, Aderlene; Barboza, Renato (O Mundo da Saúde, 2015)
The article discusses the results of an educational workshop aiming to raise awareness among health professionals in a Health Center School, leprosy’s reference unit in the central area of São Paulo. A cross-sectional, descriptive and quantitative study covering the universe of the mid-level professionals (nursing and administrative assistants) was conducted, members of an educational workshop conducted based on the problem-solving methodology of a socio constructivist basis. Data were collected through an anonymous application form at the beginning and end of the process to assess and compare the level of knowledge of professionals about the disease, subsequently submitted to descriptive analysis. The results measured in the pretest showed a high degree of ignorance about the disease and the post-test showed that there was an increase in the level of information for professionals on the category “information and knowledge”, however, it is observed that the number of correct responses was lower on the category “fears, stigmas and prejudices”, indicating the continuity of training processes to reduce vulnerabilities in the host program and suspected cases of leprosy.